Implementasi Reward dan Punishment terhadap Kinerja Karyawan Koperasi - Maulana Ramdhani; Acep Samsudin; Faizal Mulia (IPM2KPE, 2022)
The purpose of this study was to determine the effect of Reward (variable X1) and Punishment (variable X2) on Employee Performance (variable Y). This research method is using descriptive method and associative method. Data collection techniques carried out by researchers in this study were through observation, questionnaire interviews, documentation and literature study. The data analysis technique starts from data compilation, data tabulation to the testing phase. The results showed that the calculation of data categorization found that the reward value of 322 was between the low and medium criteria. Meanwhile, the value of punishment of 848 is between the medium and high criteria. In conclusion, the reward given is still low, the punishment experienced by employees is not getting higher. The performance of employees at this company has been fairly good. Keywords: Employee Performance, Punishment, Reward The purpose of this study was to determine the effect of Reward (variable X1) and Punishment (variable X2) on Employee Performance (variable Y). This research method is using descriptive method and associative method. Data collection techniques carried out by researchers in this study were through observation, questionnaire interviews, documentation and literature study. The data analysis technique starts from data compilation, data tabulation to the testing phase. The results showed that the calculation of data categorization found that the reward value of 322 was between the low and medium criteria. Meanwhile, the value of punishment of 848 is between the medium and high criteria. In conclusion, the reward given is still low, the punishment experienced by employees is not getting higher. The performance of employees at this company has been fairly good. Keywords: Employee Performance, Punishment, Reward